Ready for take-off? The economic effects of regional airport expansions in Germany - Philipp Breidenbach (Regional Studies, 2020)
Airports are an important factor of regional connectivity. Following the literature, a sufficiently dense airport network is an important determinant for growth. However, regional airports in Germany exhibit financial losses and depend on subsidies. This paper analyses the potential spillover effects of airports on the surrounding economies that may justify those subsidies by exploiting the deregulation of the European aviation market as a quasi-natural experiment. Subsequent airport expansions are evaluated in a difference-in-differences framework, making use of the exogenous shift in airport demand for regional airports due to the deregulation. Results show no evidence for spillover effects of Germany's regional airports.
Keywords: H54; R51; R42; 330; infrastructure investment; regional growth; airport effects